The effect of social media on hotel performance / Muhammad Nasri Afifi Yaacob and Muhammad Faris Azri Azman - Yaacob, Muhammad Nasri Afifi; Azman, Muhammad Faris Azri (2020)
This study aims to investigate the effect of social media on hotel performance. The secondary data were collected from various journal articles through web-based search engines related to the topic. In conclusion, there are three effects of social media on hotel performance with are for the revenue, branding and also reachability. The findings also concluded by using social media it can help the hotel to increase the revenues, create good branding image towards public and it give ease to be reach by the consumer. Therefore, in order to ensure that hotels can have a good performance from the three variables the hotel industry must focus on social media as one of the platforms that can give various advantages to increase their performance as a whole.